Zerumbone, a ginger sesquiterpene, inhibits migration, invasion, and metastatic behavior of human malignant glioblastoma multiforme in vitro. (27th May 2021) - Jalili‐Nik, Mohammad; Afshari, Amir R.; Sabri, Hamed; Bibak, Bahram; Mollazadeh, Hamid; Sahebkar, Amirhossein
Abstract: The most widespread and challenging aggressive malignant tumor in the brain is glioblastoma multiforme (GBM). GBM is characterized, in particular, by significant intratumor cell variability, high growth rates, and widespread invasiveness within the surrounding normal brain parenchyma. The present study aimed to examine the impact of the natural product Zerumbone, a promising sesquiterpenoid phytochemical from Zingiber zerumbet, on U‐87 MG GBM cells and its underlying molecular mechanisms. At sub‐lethal doses, Zerumbone exerted a concentration‐ and time‐dependent suppression of cell migration ability utilizing scratch wound closure assay; it also inhibited GBM cells' invasion using Transwell invasion assay in a concentration‐dependent fashion. The enzymatic activity of matrix metalloproteinase (MMP)‐2/‐9 and their protein expression has also been reduced by administration of Zerumbone. Furthermore, Zerumbone was revealed to downregulate the mRNA expression level of IL‐1β and MCP‐1, two genes contributing to MMPs expression. We also found that Zerumbone exerted an inhibitory effect on the expression of Akt and total p44/42 MAPK (Erk1/Erk2) against U‐87 MG cells. These findings collectively provide further proof for the possible molecular signaling basis of the antimetastatic effects of Zerumbone as a promising phytochemical, indicating a therapeutic strategy for the treatment of GBM through repression of migration, invasion, and metastasis.